Analisis Perkembangan Global Value Chain Pada Buah Tropis Global (Studi Kasus di Indonesia) - Larasati, Aulia Widya (Musamus University, 2022)
Tropical fruit is able to make a significant economic contribution and has the potential to support the development of agro-industry in the tropical fruit sector. The demand for tropical fruit is increasing which can have a beneficial effect on economic development. Indonesia is a country that has abundant natural resources potential for the development of tropical fruit products. The purpose of this study is to analyze the development of the Global Value Chain (GVC) production chain in tropical fruit, especially in Indonesia in 2015-2020. The method used is literature study and interviews with the Dean of the Faculty of Technology and Food Industry, SlametRiyadi University Surakarta, marketing manager of PT. Laris Manis, and Balitjestro Malang. The results showed that there was a GVC in Indonesian tropical fruits, specifically citrus, mango, mangosteen, and guava which resulted in increased prices for these commodities which brought value growth. In Indonesia's tropical fruit GVC, varieties such as mangosteen and guava are exported as fresh fruit, mango varieties are exported as fresh fruit and juice. Then the various types of citrus varieties are exported in processed and fresh form. There are several obstacles in the tropical fruit GVC chain such as climate, drought conditions, quality, quantity, low human resources, lack of capital, technology and investors.